GYY4137 Promotes Mice Feeding Behavior via Arcuate Nucleus Sulfur-Sulfhydrylation and AMPK Activation - Zhou, Jun; Lv, Xiao-Hui; Fan, Jun-Juan; Dang, Li-Yun; Dong, Kun; Gao, Bo; Song, Ao-Qi; Wu, Wen-Ning (Frontiers in Pharmacology, 2018)
Hydrogen sulfide (H2S) is an endogenous gaseous molecule and plays important biological and neurochemical roles in many processes such as the neural activity and immunity. The arcuate nucleus (ARC) of hypothalamus is a control center for appetite and energy metabolism. AMPK is a gauge kinase in the monitoring of energy status and regulation of energy metabolism, and it can be activated by H2S via CaMKKβ/AMPK pathway. But the role of H2S in ARC and appetite has not been reported. Here we studied the orexigenic effect of H2S and the mechanisms by means of GYY4137, a water soluble and slow-releasing donor of H2S, and protein sulfur-sulfhydrylation analysis. We demonstrated that GYY4137-derived H2S increased food intake of mice, augmented the production of neuropeptide Y (NPY), and elevated the protein sulfur-sulfhydrylation level and the activation of AMPK and CaMKKβ in ARC. Blocking sulfur-sulfhydrylation with DTT eliminated GYY4137-induced activation of AMPK and CaMKKβ. DTT and preventing AMPK activation in ARC with Compound C and Ara-A, could both attenuate the orexigenic effect of GYY4137. These findings suggest that H2S enhances appetite through protein sulfur-sulfhydrylation and the activation of AMPK and NPY function in ARC.